Public Value in Equalizing Access to Services for Vulnerable Groups Through JKN Mobile Services in Bojonegoro - Avina Febrianti; Faridatul Istighfaroh; Junadi Junadi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The transformation of digital health services through the Mobile JKN application is an important strategy in supporting equal access to health services for all people, including vulnerable groups, but its effectiveness is largely determined by the creation of public value in the implementation process. This study aims to analyze how Mobile JKN creates public value in equal access to health services for vulnerable groups in Bojonegoro Regency based on Moore's Public Value theory (1995) which includes aspects of legitimacy and support, operational capacity, and substantial value. The study used a descriptive qualitative method with data collection techniques in the form of in-depth interviews, field observations, and data analysis using NVivo with six informants consisting of community health center officers and community users of Mobile JKN. The results of the study indicate that in terms of legitimacy and support, the community is aware of the existence of Mobile JKN, but understanding and ability to use it are still low, especially among the elderly and people who do not have smartphones, so the level of public acceptance is not optimal due to uneven socialization. In terms of operational capacity, the Sumberrejo Community Health Center lacks adequate support due to limited training, low user digital literacy, and technical constraints such as weak internet connections and login failures, despite staff adapting through manual assistance, communication with BPJS Kesehatan, and the provision of Wi-Fi. In terms of substantial value, Mobile JKN has been shown to provide convenience and efficiency of services, particularly in reducing queues, but these benefits have not been felt equally by vulnerable groups. This study concludes that public value creation through Mobile JKN has not been optimal, requiring strengthened outreach, increased human resource capacity, and simplified application features to achieve more inclusive and equitable digital health services.